Cytotoxicity Evaluation Using in vitro System as a Criteria of Rational Choice of Tear Substitutes - O. I. Aleksandrova; I. N. Okolov; Yu. I. Khorolskaya; I. E. Panova; M. I. Blinova (Oftalʹmologiâ, 2018)
Purpose: to evaluate the cytotoxic effect of a wide range of lubricant eye drops on the epithelial cells of the cornea in vitro.Materials and methods. The objects of the study were 11 moisture eye drops with various preservatives and 9 moisture eye drops without preservatives. As a test-system permanent transformed cell  lines of corneal epithelial (HCEC) were used. The cytotoxicity of the  “artificial tears” was assessed by the viability of the cells, cultured in substratum containing the solutions of the evaluated eye drops.Results. The most toxic for corneal epithelial cells among the  moisture eye drops with preservatives were Lacrisifi, Slezin,  Hypromelose-P and Ophtolique®. Close to them in toxicity were  Cationorm®, Artelac® Balance and Optiv®. Eye drops Styllavit,  Systane® Ultra and Blink® contacts showed moderate toxicity.  Vismed® Light from the group of eye lubricants with preservatives  did not exert a cytotoxic effect on the cells in vitro, as well as the  non-preserved eye lubricants Hyabak®, Thealoz®, Thealoz Duo®  and EvoTears™. Cytotoxic effect on corneal epithelial cells was  detected for Hylozar Comod® and Hylo® Fresh eye drops, despite  the absence of preservatives in them.Conclusion. The study showed a principal possibility of using in vitro systems for comparative evaluation of the cytotoxic effects of various medicines with a purpose of a rational choice of moisture eye drop.